Protocatechuic acid: A novel detoxication agent of fumonisin B1 for poultry industry - Wang, Fei; Chen, Yi; Hu, Huilong; Liu, Xinyi; Wang, Yihui; Saleemi, Muhammad Kashif; He, Cheng; Haque, Md Atiqul (Frontiers in Veterinary Science, 2022)
Fumonisin B1 (FB1) is a major fusarium mycotoxin that largely contaminates feed stuffs and foods, posing a health risk to both animals and humans. This mycotoxin can enter the human body directly through contaminated food consumption or indirectly by toxins and their metabolites. In a prior study, feed-borne FB1 is one of the leading mycotoxins in breeder eggs, leading to reduced hatchability and gizzard ulceration in chicken progenies. Currently, no effective way is available to remove FB1 from feeds and human contaminated foods. Our hypothesis is that FB1 can be reduced to low risk by protocatechuic acid (PCA). In order to assess the ability of FB1 to be degraded in vivo, 1ppm of FB1 was treated with PCA, or D-Glucose, or silymarin or anti-FB1 monoclonal antibody. Our study revealed that both D-Glucose and PCA exhibited 53.4% and 71.43% degradation, respectively at 800C for 2h, while 35.15% of FB1 detoxification was determined in the Silymarin group at 600C for 0.5h. A dose-dependent manner was found after treatment with D-Glucose and PCA at 80℃ for 2h. As for detoxification of anti-FB1monoclonal antibody, the 1:3000 dilution induced significantly FB1 detoxification, accounting 25.9% degradation at 250C for 2 h. Furthermore, 50 embryonated eggs aged 11 days were divided into 10 groups, 5 eggs per group. Post treatment with PCA or D-glucose, or Silymarin or anti-FB1 monoclonal antibody, the treated samples were inoculated into albumens and monitored daily until hatching day. Consequently, 100% chickens were survival in the D-glucose group and other control groups except for FB1 control group while 80%, 80% and 60% hatching rate were found in the PCA-treated group, anti-FB1monoclonal antibody-treated group and the Silymarin-treated group. Additionally, both the FB1 group and the Silymarin-treated group yielded lower embryo growth than other groups did. Postmortem, lower gizzard ulceration index was determined in PCA-treated group and the anti-FB1monoclonal antibody-treated group compared to those of Silymarin-treated group and D-glucose-treated group. Based on above evidences, PCA is a promising detoxification to reduce FB1 contamination in poultry industry, contributing to eradication of mycotoxin residual in food chain and maintaining food security for human beings.